Twenty-fifth anniversary, eleventh of November. Memorial edition. Souvenir edition of the famous speeches of our martyrs [A.R. Parsons, A. Spies a.o.], delivered in court when asked if they had anything to be say why sentence of death should not be passed upon them, October 7, 8, and 9, 1886. November 11, 1887-1912. [With prefs by W.P. Black and L.E. Parsons] (Parsons, 1912)
In: The famous speeches of the eigt Chicago anarchists in court.